1994
DOI: 10.1037/0735-7028.25.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and law enforcement professionals: Trauma history, psychological symptoms, and impact of providing services to child sexual abuse survivors.

Abstract: A survey of 558 mental health and law enforcement professionals assessed current and past trauma experiences, exposure to traumatic client material, and the sequelae of both of those types of personal and professional trauma experiences. Results indicated that 29.8% of therapists and 19.6% of officers reported experiencing some form of childhood trauma. The two groups differed in their reports of psychological symptoms, trauma specific symptoms, and work-related post-traumatic stress disorder symptoms. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(209 citation statements)
references
References 31 publications
11
193
1
4
Order By: Relevance
“…Follette, Polusny and Milbeck on examining the impact of providing services to sexual abuse survivors also found that such work was significant to police officers [39].…”
Section: Police Personnel and Stsmentioning
confidence: 99%
“…Follette, Polusny and Milbeck on examining the impact of providing services to sexual abuse survivors also found that such work was significant to police officers [39].…”
Section: Police Personnel and Stsmentioning
confidence: 99%
“…This perhaps inadvertent balancing of clients with and without trauma issues is consistent with the recommendations of researchers on vicarious traumatization (e.g., Pearlman & Saakvitne, 1995a, 1995b. The factors that potentially contribute to adverse reactions by trauma specialists are complex (e.g., Follette, Polusny, & Milbeck, 1994;Kassam-Adams, 1995;Schauben & Frazier, 1995). However, one specific benefit of more widespread training in disaster relief and trauma work is that, when a largescale crisis arises, it would enable the unique stresses of trauma counseling to be distributed more widely among caregivers, thereby acting as a bulwark against the vicarious traumatization of any single practitioner.…”
Section: The Question Of Vicarious Traumatizationmentioning
confidence: 99%
“…En ce sens, avoir vécu, par le passé, un épuisement professionnel est considéré comme un facteur de risque pour la FC et le TV (AOcVF, 2007;Dunkley & Whelan, 2006a, b;Newell & MacNeil, 2010;RPMHTFVVC, 2005;Richardson, 2001;Stamm, 1997 (AOcVF, 2007;Baird & Kracen, 2006;Collins & Long, 2003b;Cunningham, 2003;Dunkley & Whelan, 2006b;Ga-Young, 2011;Lerias & Byrne, 2003;Nelson-Gardell & Harris, 2003;Newell & MacNeil, 2010;Pearlman & Maclan, 1995;Trippany, Wilcoxon & Satcher, 2003;VanDeusen & Way, 2006;Way, VanDeusen & Cottrell, 2007). Toutefois, certaines études soulignent plutôt l'absence de différence significative entre les symptômes des intervenants victimes de traumatismes et ceux n'en ayant pas vécu (Bober & Regehr, 2006;Folette, Polusny & Milbeck, 1994;Shauben & Frazier, 1995). Richardson (2001) (Bell et al, 2003;Richardson, 2001).…”
Section: L'histoire Personnelleunclassified
“…Richardson (2001) (Bell et al, 2003;Richardson, 2001). L'hypothèse du recours à une thérapie personnelle, qui est plutôt un facteur de protection, est mise de l'avant pour expliquer cette différence de résultats (Bober & Regehr, 2006;Folette et al, 1994;Nelson-Gardell & Harris, 2003;Hesse, 2002;Newell &MacNeil,2010).…”
Section: L'histoire Personnelleunclassified